2017
DOI: 10.1111/rec.12608
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and modeling seed germination of Mediterranean wildflowers for low input landscape restoration

Abstract: Native species are recommended for use in landscape restoration because they adapt well to the local pedo‐climatic conditions. Despite the high biodiversity in the Mediterranean, the use of native plants is hampered by the limited knowledge of their seed germination. This is particularly true for a number of plants which are appropriate for creating species‐rich herbaceous communities. In this study, seeds of 35 species were collected in different roadside and degraded sites in rural and urban areas. Two exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…The European Environment Agency [1] states that the 'quality of life in cities depends on the existence of sufficient attractive urban green areas for people and wildlife to thrive'. Recent research indicated that the biodiversity in green areas, both within and outside cities, should be increased by using native wildflowers [2][3][4]. These are defined as combinations of annual or perennial herbaceous wild species suitable for sowing in low maintenance areas [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The European Environment Agency [1] states that the 'quality of life in cities depends on the existence of sufficient attractive urban green areas for people and wildlife to thrive'. Recent research indicated that the biodiversity in green areas, both within and outside cities, should be increased by using native wildflowers [2][3][4]. These are defined as combinations of annual or perennial herbaceous wild species suitable for sowing in low maintenance areas [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These are defined as combinations of annual or perennial herbaceous wild species suitable for sowing in low maintenance areas [5][6][7][8]. The multifunctional role of wildflowers is already well-known, as they help promote biodiversity and restore habitat, requiring low-input management [3,6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dormancy linked to waterproofness of the seed coat (physical dormancy according to Baskin and Baskin 2004) affects several families of angiosperms and many members of the Fabaceae family (Silveira and Fernandes 2006;Gresta Communicated by M. Horbowicz. et al 2011;Venier et al 2012;Hosseini et al 2013;Toscano et al 2017). Due to the capability to fix nitrogen (N), the Fabaceae species exert an important role within the wild plant community, but also as crops for sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%